Analisis Usability Testing pada SITIDES Menggunakan System Usability Scale dan PIECES Framework - Valian Yoga Pudya Ardhana (PDSI, 2022)
SITIDES Bengkaung Village is a website-based integrated system owned by Bengkaung Village located in West Lombok Regency, West Nusa Tenggara (NTB) Province under the management of village officials. All information related to Bengkaung Village is displayed on SITIDES Bengkaung Village. However, since the system was officially used, there has never been an evaluation and testing of the level of user satisfaction, in this case the manager of SITIDES Bengkaung Village, so a usability analysis is needed which in this case uses two methods, namely the PIECES Framework and the System Usability Scale. The purpose of this evaluation and testing is to measure the level of satisfaction of SITIDES users in Bengkaung Village, in this case the managers of which there are 9 people who have different access rights. Based on the research that has been done, the results of the analysis using the Pieces Framework method are a value of 4.36 obtained from the average value of 6 domains. This value is in the very satisfied category. While the results of the user satisfaction level of SITIDES Bengkaung Village using the System Usability Scale method are obtained a value of 77.78 where the value for the acceptability range version is Acceptable, while the grade scale results from the level of user acceptance are included in class B. Based on the measurement results using 2 The method obtained almost the same results, which showed that the users were very satisfied with the SITIDES system in Bengkaung Village so that the system was very feasible to use.